THE DISCOVERY OF MERCURY-RESISTANT BACTERIA KLEBSIELLA PNEUMONIAE ISOLATED FROM SARIO RIVER ESTUARY THAT CAN BE USED TO DETOXIFY INORGANIK MERCURY WASTES - Fatimawali, Fatimawali (PHARMACON, 2013)
Mercury is well known for its high toxicity and strong affinity toward the thiol group of proteins. Mercury-resistant bacteria can be used for detoxify mercury wastes due to the ability of these bacteria to reduce toxic inorganic mercury into mercury metal which is volatile and less toxic. The aim of this study was the selection of bacterial strains resistant to inorganic mercury, as well as to show their capacity to reduce mercury in pure culture media Nutrient Broth. Six strains bacteria was isolated and one of them, A1.1.1. isolate was selected for its capacity to reduce mercury HgCl2 in culture media nutrient broth. The one bacterial strains belong to the spesies Klebsiella pneumoniae. Inoculated in pure culture, these strain showed a mercury reduction of 75% in 1 hour, 92% in 12 hours, and 99,4% in 24 hours. Therefore, this bacterium could be useful in detoxification of inorganic mercury wastes. Keywords : Bacteria, Klebsiella pneumoniae, Hg-resistant, detoxification